2007
DOI: 10.1093/ejo/cjl081
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic pain: from causes to management--a review

Abstract: Orthodontic pain, the most cited negative effect arising from orthodontic force application, is a major concern for parents, patients, and clinicians. Studies have reported this reaction to be a major deterrent to orthodontic treatment and an important reason for discontinuing treatment. Surprisingly this area, which requires attention in clinical practice as well as in research, is ignored as evidenced by the scarcity of publications on the topic in comparison with other areas of orthodontic research. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
352
2
40

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(413 citation statements)
references
References 74 publications
19
352
2
40
Order By: Relevance
“…The trigeminal nucleus caudalis (Vc) plays important roles in the orofacial nociception (Balam et al, 2005;Krishnan, 2007). Recent studies have shown that COX2 in central nervous The summary histogram showed the expression ratio of COX2 protein level normalized to b-actin in the same sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trigeminal nucleus caudalis (Vc) plays important roles in the orofacial nociception (Balam et al, 2005;Krishnan, 2007). Recent studies have shown that COX2 in central nervous The summary histogram showed the expression ratio of COX2 protein level normalized to b-actin in the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…The trigeminal nucleus caudalis (Vc) plays important roles in the regulation and/or transmission of the sustained orofacial nociceptive signals (Balam et al, 2005;Krishnan, 2007). Previous studies showed that experimental tooth movement induced intense Fos response in Vc (Yamashiro et al, 1997;Aihara et al, 1999;Magdalena et al, 2004), suggesting a correlation between Vc activation and painful sensation resulting from tooth movement.…”
mentioning
confidence: 99%
“…The adjusted mean difference was 0.14 (95% confidence interval -0.13 to 0.41), p=0.32. Ibuprofen use 13 The protocol allowed patients in the intervention (chewing gum) group to take ibuprofen if they felt pain relief following chewing gum use was insufficient. Ibuprofen use was recorded on the day itself (2h, 6h, bedtime) and for each of the subsequent three days, for each visit.…”
Section: Painmentioning
confidence: 99%
“…Why orthodontic pain occurs is still unknown, but it has been described in a review by Krishnan (2007) 13 as possibly arising as a result of the pressure, ischaemia and inflammation induced within the periodontal ligament during the induced tooth movement. This then leads to changes in blood flow, the release of mediators such as prostaglandins and a resultant hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…1 The noxious stimulus of orthodontic pain is the compression of the periodontal ligament by the tooth, resulting in an inflammatory response mediated by release of chemical mediators such as histamines, bradykinins, serotonin, substance P, cytokines, and prostaglandins. 2,3 Surveys of orthodontic patients have brought to light that pain is among the most cited negative effects of orthodontic therapy, even when compared to that experienced after other invasive procedures, such as extractions, etc. [4][5][6][7][8] There have been a few reported cases in which this pain reaction has proved to be a major deterrent to orthodontic treatment and an important reason for discontinuation of treatment.…”
Section: Introductionmentioning
confidence: 99%